Credit Ratings and Corporate Information Production: Evidence from Sovereign Downgrades - Wang, Daisy (Sicong); Xie, Wensi (Journal of Financial and Quantitative Analysis, 2022)
Abstract Exploiting exogenous variations in corporate ratings due to sovereign credit downgrades and sovereign ceiling policies, we assess how firms respond to a reduction in credit ratings. We find that firms bounded by the sovereign ceiling significantly increase information production in response to a sovereign downgrade. The effects are stronger for firms relying more heavily on external finance and operating in a more opaque environment. Enhanced information production, in turn, affects firms’ subsequent access to bond markets. These findings suggest that firms actively manage information environments to maintain access to public debt markets.